Comparison of Polypoidal Choroidal Vasculopathy Lesion Sizes Measured on Multicolor Imaging and Indocyanine Green Angiography - Lim, Louis W. (Transl Vis Sci Technol, 2021)
PURPOSE: To evaluate the areas of lesion components of polypoidal choroidal vasculopathy (PCV) measured using multicolor imaging compared to indocyanine green angiography (ICGA). METHODS: In a prospective study of 50 consecutive treatment-naïve PCV patients, multicolor imaging and ICGA were performed. The images were independently graded by reading center-certified retinal specialists to confirm the diagnosis of PCV and identify lesion components. The areas of the respective lesion components were compared. RESULTS: The mean age of the participants was 67.8 years. PCV was diagnosed in 96% of eyes using multicolor imaging. The mean numbers of polypoidal lesions identified using ICGA and multicolor were 4.0 and 2.1, respectively (P < 0.001), with mean total polypoidal lesion areas of 0.32 mm(2) versus 0.30 mm(2) (P = 0.727). The area of the branching vascular network (BVN) on ICGA was 7.8 mm(2) compared to 5.7 mm(2) on multicolor imaging (P = 0.289). Patients with four or more polypoidal lesions on ICGA had larger differences in total lesion area between ICGA and multicolor imaging (4.07 vs. –0.70 mm(2), p = 0.039). Those with total lesion area ≥ 2.0 mm(2) on ICGA had larger differences in mean polypoidal lesion number compared to those with smaller areas (2.2 vs. 0.5; P = 0.026). CONCLUSIONS: Multicolor imaging is a useful, noninvasive adjunct for detecting PCV lesion components, revealing lesion areas similar to but generally smaller than those seen on ICGA. This is important to consider when making treatment decisions with different imaging modalities TRANSLATIONAL RELEVANCE: New features seen on multicolor imaging can aid in the diagnosis and treatment of PCV.